PENINGKATAN KEDISIPLINAN DAN PRESTASI BELAJAR SEJARAH MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) SMA NEGERI 1 SEWON - Marharjono Marharjono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2016)
This research is intended to improve 1) the students’ learning discipline through a Type of Cooperative Teaching and Learning Method Namely Teams Games Tournament (TGT) 2) the students’ learning achievement through a Type of Cooperative Teaching and Learning Method Namely Teams Games Tournament (TGT). This study is an action research which used two cycles. The subject or the study was XI IPS 2 Student of SMA Negeri 1 Sewon on the academic years of 2015/2016. The data were collected by usingthe techniques of observation, questionnaire, and test of history lesson. The data analyzing technique used in this research was descriptive comparative technique. The result of the study shows that the application of Teams Games Tournament method is able to increase: 1) the students’ learning discipline, categorized good and very good, at the pre-cycle there were 14 students (53.8%), at the cycle 1 increasing from 15 students (57.7%) to be 20 students (76.9%) at the first and second meetings, and at the cycle 2 increasing from 23 students (88.5%) to be 25 students (96.2%) at first and second meetings, 2) the achievement in learning history, increasing from the means 74.38 and passing index 65.38% at the pre-cycle to be the means 76.46 and the passing index 73.08% at the cycle 1, and at the cycle 2 the means increased to be 84.35 and the passing index increased to be 88.46%. Therefore, the application of cooperative learning method Teams Games Tournament (TGT) is able to improve the learning discipline and history learningachievement of XI IPS 2 Student of SMA Negeri 1 Sewon on the academic years of 2015/2016.